An eye on eye development - Sinn, Rebecca; Wittbrodt, Joachim (Mechanisms of development, 2013)
The vertebrate eye is composed of both surface ectodermal and neuroectodermal derivatives that evaginate laterally from an epithelial anlage of the forming diencephalon. The retina is composed of a limited number of neuronal and non-neuronal cell types and is seen as a model for the brain with reduced complexity. The eye develops in a stereotypic manner building on evolutionarily conserved molecular networks. Eye formation is initiated at the onset of gastrulation by the determination of the eye field in the anterior neuroectoderm. Homeobox transcription factors, in particular Six3 are crucially involved in the establishment and maintenance of retinal identity. The eye field expands by proliferation as gastrulation proceeds and is initially confined to a single retinal primordium by the differential activity of specifying transcription factors. This central field is subsequently split in response to secreted factors emanating from the ventral midline. Concomitant with medio-lateral patterning at the onset of neurulation, morphogenesis sets in and laterally evaginates the optic vesicle. Strikingly during this process the neuroectoderm in the eye field transiently loses epithelial features and cells migrate individually. In a second morphogenetic event, the vesicle is transformed into the optic cup, concomitant with onset and progression of retinal differentiation. Accompanying optic cup morphogenesis, neural differentiation is initiated from a retinal signalling centre in a stereotypic and species specific manner by secreted signalling factors. Here we will give an overview of key events during vertebrate eye formation and highlight key players in the respective processes.